Early instrumental air pressure and temperature measurements for Rovereto and Bolzano/Bozen (1800-1873) - Yuri Brugnara; Michael Horn; Isabella Salvador (PANGAEA, 2023)
We provide two instrumental records of air pressure and temperature for the Alpine cities of Rovereto and Bolzano/Bozen, covering the periods 1800-1839 and 1842-1873, respectively. They were measured by local physics teachers and digitized at the University of Bern from a handwritten weather diary and a local newspaper. In addition to the raw (sub-daily) data, we provide daily and monthly means together with a quantitative estimation of their uncertainty. The data were converted to modern units, quality controlled, and homogenized.